Implementation of a direct observation and feedback tool using an interprofessional approach: a pilot study. Issue 4 (4th July 2021) - Thompson Buum, Heather; Dierich, Mary; Adam, Patricia; Hager, Keri D.
ABSTRACT: Primary care trainees must learn how to communicate effectively with patients during brief outpatient encounters, and direct observation and feedback is necessary to improve these skills. At the same time, programs are seeking more interprofessional learning opportunities for skills that transcend professions. We sought to assess the feasibility of implementing a direct observation tool, the Patient Centered Observation Form (PCOF), for communication training across three professions at the graduate level. The PCOF was introduced to trainees at an interprofessional workshop, while faculty completed PCOF training online or in person. Following use of the PCOF, we surveyed participants to determine if using the PCOF increased a) trainee-reported confidence in providing patient-centered communication, and b) faculty-reported confidence in giving feedback about patient-centered communication. The PCOF appears to be a useful adjunct to standard precepting for teaching patient-centered communication skills, extending beyond medical residents to pharmacy residents and less so, to advanced practice nursing students. In addition, PCOF training and implementation can successfully occur simultaneously across disciplines, leveraging resources and encouraging interprofessional learning.